PENGARUH PEMBERIAN TERAPI AKUPRESUR TERHADAP MUAL MUNTAH PASCA OPERASI SECTIO CAESARIA DENGAN ANESTESI SPINAL DI RSUD KABUPATEN ACEH TAMIANG - Setiawan, Bambang (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2023)
The number of deliveries by caesarean section in Indonesia is quite high, regional anesthesia is the main choice for sectio caesarea, postoperative nausea and vomiting are physiological reactions that are experienced after surgery, the treatment for postoperative nausea and vomiting can be given pharmacology and non-pharmacology. Pharmacological therapy with antiemetic administration, while non-pharmacological therapy with acupressure. To determine the effect of giving acupressure therapy on nausea and vomiting after cesarean section surgery with spinal anesthesia at Aceh Tamiang District Hospital.The type of research used was quasi-experimental with a prepost test with control group design. Respondents will be given pretest and posttest treatment with a Gordon measurement scale, in the intervention group will be given acupressure therapy. The sample in this study was 48 respondents in the intervention group and 48 respondents in the control group. The sampling technique used was consecutive sampling. Data collection in April-May 2023.The results of data collection were processed using the Wilcoxon test and the Mann Whitney test. The results of the Wilcoxon test in the intervention group were p=0.000 (p<0.05) and in the control group p=0.000 (p<0.05). The Mann Whitney test results obtained p=0.000 (p<0.05), so that Ha was accepted.There is an effect of giving acupressure therapy on the level of nausea and vomiting after sectio caesarea surgery in Aceh Tamiang District Hospital.